2022
DOI: 10.3389/fsurg.2022.862632
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Recovery Outcomes for Obese Patients Undergoing General Anesthesia: A Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeThis study was performed to assess the postoperative recovery outcomes in obese patients undergoing general anesthesia.MethodsThe eligible studies were identified from PubMed, EmBase, and the Cochrane library until December 2020. The standard mean differences (SMDs) with 95% confidence intervals (CIs) were used to calculate the role of desflurane, sevoflurane, and propofol on recovery outcomes, and the analyses using the random-effects model.ResultsEleven randomized controlled trials involving 713 obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, TIVA has been associated with a lower incidence of postoperative nausea and vomiting [36]. In patients who are obese, the use of volatile anaesthetic agents has been reported to reduce the time it takes for patients to become fully awake, but this reduction may not be considered clinically significant and remains a topic of debate [37, 38]. Lastly, a recent study conducted in our institution suggested the feasibility of very early initiation of postoperative rehabilitation in the post‐anaesthesia care unit following major thoracic surgery after general anaesthesia with TIVA [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TIVA has been associated with a lower incidence of postoperative nausea and vomiting [36]. In patients who are obese, the use of volatile anaesthetic agents has been reported to reduce the time it takes for patients to become fully awake, but this reduction may not be considered clinically significant and remains a topic of debate [37, 38]. Lastly, a recent study conducted in our institution suggested the feasibility of very early initiation of postoperative rehabilitation in the post‐anaesthesia care unit following major thoracic surgery after general anaesthesia with TIVA [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TIVA has been associated with a lower incidence of postoperative nausea and vomiting [36]. In patients who are obese, the use of volatile anaesthetic agents has been reported to reduce the time it takes for patients to become fully awake, but this reduction may not be considered clinically significant and remains a topic of debate [37,38].…”
Section: Kotani Et Al Reported a 10% Increase In Mortality Withmentioning
confidence: 99%
“…fatty tissue [17]. Figure 3b shows the 80% contextsensitive decrement time (CSDT) at a wide range of BMI.…”
Section: Key Pointsmentioning
confidence: 99%
“…Regarding delayed emergence after continuous infusion, propofol has been thought to sometimes have prolonged effects in obese patients because of propofol's high lipophilicity with distribution into fatty tissue [17]. Figure 3b shows the 80% context-sensitive decrement time (CSDT) at a wide range of BMI.…”
Section: Propofolmentioning
confidence: 99%
“…Patients with obesity often exhibit an increased proportion of body fat and reduced blood flow through adipose tissue (1). When dosing anesthetic drugs based on actual body weight, the apparent volume of drug distribution and metabolic rate can be significantly impacted, affecting the quality and duration of awakening resulting in accumulation and prolonged duration in clinical anesthesia for patients with obesity (2)(3)(4). Suggestions have been made to administer drugs to patients with obesity based on their defatted body weight to adjust anesthetic dosage (5).…”
Section: Introductionmentioning
confidence: 99%